OPTIMIZATION OF BREAKING DORMANCY OF SUGAR PALM SEEDS (Arenga Pinnata Merr.) THROUGH PHYSICAL SCARIFICATION WITH POSITION VARIATIONS - Sari, Afrima; Anwar, Aswaldi; Ramadhan, Nugraha; Hayati, P.K. Dewi; Zainal, Aprizal; Prawinata, Pagil; Rahman, Atzim Baitur (Agros Journal of Agriculture Science, 2024)
The germination process is the key to plant phenology, which significantly influences the success of early plant growth. Some seeds have a dormancy, so the germination process is hampered or does not occur. However, dormancy-breaking treatments in plants have been widely reported, such as breaking the dormancy of sugar palm seeds through physical scarification. This research aims to determine the best scarification position to break the dormancy of sugar palm seeds. This research was carried out at the Seed Technology Laboratory, Faculty of Agriculture, Universitas Andalas from July to October 2023. The design was completely randomized with scarification in two position variations, the operculum (A1) and dorsal (A2) points, repeated thrice. The results showed that the position of seed scarification affected the emergence time of cotyledon petioles and coleoptiles, germination capacity, and seed moisture content. Scarification at the operculum point requires a dormancy break of 16 DAP (Days After Planting) compared to 29 DAP for the dorsal. Seed viability was good in seeds sacrificed at the operculum point, with a germination percentage of 81.94%. Keywords: dorsal, operculum, cotyledon petiole